El efecto del uso de prendas de color rojo en la evaluación del atractivo (2016)
The objective of the present study is to determine the effect of red color, on the evaluation that people make about attractiveness of a person who wear it. To achieve this objective, an experimental method was used. The tentative results in the present investigation are mainly: first, it is expected that people consider the person who wears a red garment to be more attractive than those who wear a green, black or white color. Second, it is expected that there will be a difference between the sexes about the assessment of attractiveness.--Tomado del Formato de Documento de Grado.